The Rising Burden of Non-Communicable Diseases Among HIV-Positive Individuals: A Clinical Analysis. - Singh, Alisha; Daksh, Shashi (Journal of Neonatal Surgery, 2025)
The medical communities worldwide achieved major progress after introducing antiretroviral therapy which turned fatal HIV into sustainable chronic condition treatment. The successful treatment of HIV through antiretroviral therapy now leads to worrying new difficulties because HIV-positive persons face higher frequencies of non-communicable diseases when compared to their general population peers. A cross-sectional research evaluated the HIV-Non-Communicable Disease relationship by measuring 900 participants (including 300 HIV-positive along with 600 HIV-negative controls) from different healthcare facilities. The research showed that HIV-positive individuals experienced higher occurrences of cardiovascular diseases, diabetes, and respiratory conditions than the control group while revealing that 62% of them presented two or more concurrent NCDs. The research presented results regarding HIV infection and treatment and their effects on NCD development while showing substantial impact on medical costs and patient health outcomes. Different patterns of NCD features emerged within HIV-positive subjects so we suggest establishing specialized assessment and treatment methods. The study demonstrates the necessity of establishing healthcare systems which simultaneously manage HIV and prevent NCDs for these vulnerable patients.